Urgensi Pembaharuan Tindak Pidana Penyalahgunaan Senjata Api - Sayogaramasatya, I Gede; Mertha, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 1 (2023), 2023)
he purpose of this paper is to find out the urgency of reforming firearms crimes regarding abuse in the use of firearms in Indonesia today (Ius Constitutum) so that the renewal of criminal law against the use of firearms is in accordance with the aspired law (Ius Constituendum). The research method used in this paper is a normative legal research method. By using a statutory approach (Statute Approach). The search for this legal material is a document study. The results of the study indicate that the regulation of criminal acts of abuse of firearms is currently regulated (ius constitutum) which mentions the revocation of licenses and the seizure of firearms in the event of misuse, the regulation is not clear or it can be said that there is a vagueness of norms. Regarding the renewal of criminal law on the regulation of criminal acts of misuse of firearms in the future (ius constituendum), the author feels that this needs to be done. The reform in question is the need for regulations regarding the misuse of firearms to be regulated in a legal codification in the form of a law. In addition, various cases of misuse of firearms that have occurred so far seem to confirm that legal uncertainty in regulating the use of firearms has disrupted the public's sense of security. Tujuan tuisan ini adalah mengetahui urgensi pembaharuan tindak pidana senjata api mengenai penyalahgunaan dalam penggunaan senjata api di Indonesia saat ini ( Ius Constitutum) sehingga pembaharuan hukum pidana terhadap penggunaan senjata api sesuai dengan hukum yang dicita-citakan (Ius Constituendum). Metode penelitian yang digunakan dalam tulisan ini adalah metode penelitian hukum normatif. Dengan menggunakan pendekatan perundang-undangan (Statute Approach). Penelusuran terhadap bahan hukum ini ialah studi dokumen. Hasil penelitian menunjukan bahwa Pengaturan tindak pidana penyalahgunaan senjata api yang diatur saat ini (ius constitutum) yang menyebutkan mengenai pencabutan izin dan perampasan senjata api bilamana terjadi penyalahgunaan, belum jelas pengaturannya atau dapat dikatakan terdapat kekaburan norma. Terkait pembaharuan hukum pidana terhadap pengaturan tindak pidana penyalahgunaan senjata api di masa mendatang (ius constituendum), penulis merasa hal tersebut perlu dilakukan. Pembaharuan yang dimaksud adalah perlunya pengaturan mengenai penyalahgunaan senjata api ini diatur dalam satu kodifikasi hukum berbentuk Undang- Undang. Selain itu, berbagai kasus penyalahgunaan penggunaan senjata api yang terjadi selama ini seolah-olah menjadi penegas bahwa ketidakpastian hukum dalam pengaturan penyalahgunaan senjata api tersebut mengakibatkan terganggunya rasa aman publik.